Clinical Characteristics and Inflammatory Immune Responses in COVID-19 Patients With Hypertension: A Retrospective Study - Wu, Chaoran; Qu, Guangbo; Wang, Lei; Cao, Shiyu; Xia, Dandan; Wang, Baolong; Fan, Xiaoyun; Wang, Changhui (Frontiers in Pharmacology, 2021)
Coronavirus disease (COVID-19) patients with cardiovascular and metabolic disorders have been found to have a high risk of developing severe conditions with high mortality, further affecting the prognosis of COVID-19. However, the effect of hypertension and angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blocker (ARB) agents on the clinical characteristics and inflammatory immune response in COVID-19 patients are still undefined. In this study, 90 COVID-19 patients were divided into hypertension and non-hypertension groups. The hypertension group was divided into well-controlled and poorly controlled subgroups based on blood pressure levels; moreover, hypertensive patients were also divided into ACEI/ARB and non-ACEI/ARB subgroups according to the administration of ACEI/ARB antihypertensive agents. Clinical characteristics of and inflammatory immune biomarker levels in the different groups of COVID-19 patients were compared, and the association between the combined effect of hypertension with ACEI/ARB antihypertensive agents and the severity of COVID-19 was examined. The results showed that levels of aminotransferase (AST) and hs-cTnI were higher in hypertension group compared with non-hypertension group, The long-term use of ACEI/ARB patients had statistically significant lower AST, low-density lipoprotein cholesterol (LDL-C) and oxygen uptake and lower white cell count, neutrophil count, lever of CD4, CD8, CRP and PCT but without statistically significance. In addition, compared with COVID-19 patients without hypertension, hypertension patients without using ACEI/ARB had a higher risk of developing severity of COVID-19 (for poorly controlled patients: OR=3.97, 95%CI=1.03–15.30; for well controlled patients: OR=6.48, 95%CI=1.77–23.81). Hypertension could cause organs damage to COVID-19 patients, but the long term of using ACEI/ARB agents may be beneficial to alleviate this injury.